Nasal microbiome in relation to olfactory dysfunction and cognitive decline in older adults - Huiling Song; Jiaojiao Zou; Zhonghan Sun; Yanni Pu; Wenhao Qi; Liang Sun; Qian Li; Changzheng Yuan; Xiaofeng Wang; Xiang Gao; Yan Zheng (Translational Psychiatry)
Abstract Emerging evidence has highlighted that olfactory dysfunction, a common feature of aging, is increasingly linked to cognitive decline in older adults. However, research on the underlying mechanism, particularly the role of nasal microbiome, remains limited. In this study, we investigated the associations between olfactory function, the nasal microbiome, and cognition among 510 older adults with an average age of 77.9 years. Olfactory function was assessed using the brief Chinese Smell Identification Test, and cognitive assessments were conducted via the Mini-Mental State Examination and the Revised Hasegawa Dementia Scale. Nasal microbiome profiles were generated through 16S RNA gene sequencing. We observed that olfactory dysfunction (i.e., hyposmia) was associated with a higher richness of nasal bacteria, and such observation was replicated in an external dataset. A total of 18 nasal bacterial genera were identified to be associated with olfactory function, with eight genera such as Acidovorax and Morganella being enriched in the hyposmic group. A composite microbial index of nasal olfactory function significantly improved the reclassification accuracy of traditional risk model in distinguishing hyposmic from normosmic participants (P = 0.008). Furthermore, participants with a nasal biotype dominated by Corynebacterium had a lower prevalence of mild cognitive impairment compared to those dominated by Dolosigranulum or Moraxella. Our findings suggested that the nasal microbiome may play a role in the association of olfactory function with cognition in older adults, providing new insights into the microbial mechanisms underlying hyposmia and cognitive decline.